Bibliometric Analysis of Higher Order Thinking Skills (HOTS)-Based E-Module Research in Education from 2015 to 2025 Using VOSviewer - Naila Rahma Alya Adinda; Kurnia Adityarini Putri Handayani; Irfandi Maulana Firdaus; Maria Vernanda; Nayfa Aulia Az-Zahra; Nur Hafiza Kholistiyani (NAJAHA, 2025)
Higher Order Thinking Skills (HOTS) are essential competencies in 21st-century education, where e-modules serve as a crucial innovation in learning media. However, there is no comprehensive mapping covering research trends up to 2025. This study aims to analyze the bibliometric development of HOTS-based e-module research in education from 2015 to 2025. The research method employed is bibliometric analysis using VOSviewer software. Publication data were collected from the Google Scholar database via Publish or Perish. The results reveal a significant upward trend in publications over the last decade. Based on the network visualization, the major clusters connect e-modules to critical thinking, problem-solving, and digital literacy. The overlay visualization shows a shift in research focus from conventional module development to the integration of interactive technology and artificial intelligence in recent years (2023–2025). Density visualization identifies that e-module topics in Science and Mathematics are highly saturated, while research opportunities in the humanities and inclusive education remain widely open. In conclusion, HOTS-based e-module research continues to evolve dynamically and is increasingly integrated with the latest educational technologies.